IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN BAGI PENDUDUK MISKIN DI PUSKESMAS ONDONG KECAMATAN SIAU BARAT KABUPATEN SIAU TAGULANDANG BIARO - Kansil, Okjen Malendes (Sam Ratulangi University, 2014)
ABSTRAK Policy Implementation Health Service For Poor People In Puskesmas Ondong Subdistrict Siau Barat Regency Siau Tagulandang Biaro Beneath The Guidance By Prof. Dr. Drs. P. Rumapea, M.Si Dr. Dra. Joyce Rares, M.SiRegency Siau Tagulandang Biaro doesn’t have region regulation ( PERDA) about Healthy service to give to people. In fact showed the puskesmas Ondong still demerit human resources about medic staff.This research use qualitative method. A research focus are : 1) The process of policy implementation healthy service refer to from four aspect of influence policy implementation is communication, capacity resources, disposition, and bureaucracy structure. 2) The result of policy implementation healthy service refer from effectiveness side and efficiency.Data source / informant 14 people is servicer element and service receiver this research consist of four dimensions are communication, capacity resources, dipostion, and structure organization / bureaucracy. The condusion can take from this research result is geberal scale.Policy Implementation healthy service for poor people in puskesmas Ondong Subdistrict Siau Barat Regency Siau Tagulandang Biaro is good, but not optimum that is from capcity resources side. Puskesmas Ondong still demerit medic staff ( doctor, nurse, midwife and medic equiptment ). Recommendation idea to government Regency Siau Tagulandang Biarro in order to make Region Regulation ( PERDA ) about healthy service. Agree with foor indicators problem research, in order to government can more increase management service to people is preparing human resources (SDM) in this matter medic staff be able to give action agree with competence belong in a effective and efficient in order to hopely.Keywords : Policy Implementation Health Service For Poor People In Puskesmas Ondong Subdistrict Siau Barat Regency Siau Tagulandang Biaro.